Gut Commensal Parabacteroides goldsteinii MTS01 Alters Gut Microbiota Composition and Reduces Cholesterol to Mitigate Helicobacter pylori-Induced Pathogenesis - Lai, Chih-Ho; Lin, Tzu-Lung; Huang, Mei-Zi; Li, Shiao-Wen; Wu, Hui-Yu; Chiu, Ya-Fang; Yang, Chia-Yu; Chiu, Cheng-Hsun; Lai, Hsin-Chih (Frontiers in Immunology, 2022)
Helicobacter pylori infection is closely associated with various gastrointestinal diseases and poses a serious threat to human health owing to its increasing antimicrobial resistance. H. pylori possesses two major virulence factors, vacuolating cytotoxin A (VacA) and cytotoxin-associated gene A (CagA), which are involved in its pathogenesis. Probiotics have recently been used to eradicate H. pylori infection and reduce the adverse effects of antibiotic-based therapies. Parabacteroides goldsteinii MTS01 is a novel next-generation probiotic (NGP) with activities that can alleviate specific diseases by altering the gut microbiota. However, the mechanism by which P. goldsteinii MTS01 exerts its probiotic effects against H. pylori infection remains unclear. Our results showed that administration of P. goldsteinii MTS01 to H. pylori-infected model mice altered the composition of the gut microbiota and significantly reduced serum cholesterol levels, which mitigated H. pylori-induced gastric inflammation. In addition, the pathogenic effects of H. pylori VacA and CagA on gastric epithelial cells were markedly abrogated by treatment with P. goldsteinii MTS01. These results indicate that P. goldsteinii MTS01 can modulate gut microbiota composition and has anti-virulence factor functions, and thus could be developed as a novel functional probiotic for reducing H. pylori-induced pathogenesis.